Primary stroke prevention worldwide: translating evidence into action. (January 2022) - Owolabi, Mayowa O; Thrift, Amanda G; Mahal, Ajay; Ishida, Marie; Martins, Sheila; Johnson, Walter D; Pandian, Jeyaraj; Abd-Allah, Foad; Yaria, Joseph; Phan, Hoang T; Roth, Greg; Gall, Seana L; et al.
Summary: Stroke is the second leading cause of death and the third leading cause of disability worldwide and its burden is increasing rapidly in low-income and middle-income countries, many of which are unable to face the challenges it imposes. In this Health Policy paper on primary stroke prevention, we provide an overview of the current situation regarding primary prevention services, estimate the cost of stroke and stroke prevention, and identify deficiencies in existing guidelines and gaps in primary prevention. We also offer a set of pragmatic solutions for implementation of primary stroke prevention, with an emphasis on the role of governments and population-wide strategies, including task-shifting and sharing and health system re-engineering. Implementation of primary stroke prevention involves patients, health professionals, funders, policy makers, implementation partners, and the entire population along the life course.